In vitro models of HIV-1 infection of the central nervous system. (2020) - Faia, Celeste; Plaisance-Bonstaff, Karlie; Peruzzi, Francesca
Abstract : Neurocognitive disorders associated with HIV-1 infection affect more than half of persons living with HIV (PLWH) under retroviral therapy. Understanding the molecular mechanisms and the complex cellular network communication underlying neurological dysfunction is critical for the development of an effective therapy. As with other neurological disorders, challenges to studying HIV infection of the brain include limited access to clinical samples and proper reproducibility of the complexity of brain networks in cellular and animal models. This review focuses on cellular models used to investigate various aspects of neurological dysfunction associated with HIV infection.